Miti e immagini cartesiane - Siegrid Agostini (Noctua)
Recent historiography has shown that Descartes remains a prominent figure in philosophical discourse and that a multitude of prejudices have arisen around his persona, which have contributed over time to the creation of an often stereotyped and, in some cases, distorted image of him and his most famous and influential doctrines. It is therefore essential to take stock of the state of historiographical research on Descartes in recent years. In this context, I have tried to draw attention to some recently published volumes, with the aim of enabling the reader to approach the study of this great philosopher with greater awareness. This can be achieved both through the author’s internal analysis of his work and the comparison with other philosophers and scholars who were his contemporaries.